1999
DOI: 10.1007/s001050050961
|View full text |Cite
|
Sign up to set email alerts
|

Langzeitergebnisse nach Strahlentherapie beim lokal rezidivierten und metastasierten malignen Melanom

Abstract: The 20-year radiotherapy (RT) experience in patients with locally advanced, recurrent or metastatic malignant melanoma (MM) is analyzed with respect to different endpoints and prognostic factors. From 1977 to 1995, 2917 consecutive patients were entered in our MM registry. RT was indicated in 121 patients (56 females, 65 males) for palliation in advanced MM stages. The histology of the primary lesion was nodular in 51, superficial spreading in 35, acral-lentiginous in 8 and lentigo maligna in 4 patients); 22 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
6
0
1
Order By: Relevance
“…Thus, nowadays malignant melanomas are no longer regarded as being radio‐resistant and clinical experience with radiotherapy of locoregional and distant metastases show a remission rate of up to 67%. 14–17 This is higher than achieved with most polychemoimmunotherapies. Multi‐variant analysis showed that the clinical tumour stage (UICC stage) is the most important and only independent prognostic factor for the initial and long‐term tumour control and survival after radiotherapy.…”
Section: Radiotherapymentioning
confidence: 86%
See 2 more Smart Citations
“…Thus, nowadays malignant melanomas are no longer regarded as being radio‐resistant and clinical experience with radiotherapy of locoregional and distant metastases show a remission rate of up to 67%. 14–17 This is higher than achieved with most polychemoimmunotherapies. Multi‐variant analysis showed that the clinical tumour stage (UICC stage) is the most important and only independent prognostic factor for the initial and long‐term tumour control and survival after radiotherapy.…”
Section: Radiotherapymentioning
confidence: 86%
“…Radiobiological and clinical data indicate a better tumour response to hypofractionated radiotherapy (< 5 fractions per week) with higher single doses (up to 9 Gy) than with conventional fractionated radiotherapy (5 × 2 Gy/week). This is contradicted by newer randomized studies (Radiation Therapy Oncology Group 83–05) 13,17 , 18…”
Section: Radiotherapymentioning
confidence: 98%
See 1 more Smart Citation
“…Conversely, it is more often utilized in patients with high-risk local-regional recurrence, including patients with desmoplastic melanoma or high nodal disease burden [ 60 , 61 , 62 , 63 ]. However, RT has a beneficial role in the palliation of local symptoms, such as bleeding, pain and fungating infections, which may result from extensive IT disease [ 64 , 65 , 66 ]. While not curative, high RT doses (>30 Gy) have been shown to obtain longer disease-free survival rates and overall survival compared to patients treated with lower RT doses (≤30 Gy) [ 67 ].…”
Section: Radiationmentioning
confidence: 99%
“…(127) Radiotherapy is another well recognised treatment modality in the management of this disease. (233,236) This study demonstrates that a combined regimen produces high rates of robust lesion control without a clinically significant increase in toxicity. Compared to previous studies with PV-10 alone, combined therapy using PV-10 and XRT may improve clinical outcomes through a reduction in tumour volume associated with a more durable ORR secondary to improved CR and PR.…”
Section: Discussionmentioning
confidence: 74%